Efisiensi Biaya Pengendalian Bahan Baku Berdasarkan Eoq Pada Umkm Pia Mirah - Romansyah Sahabuddin; Sitti Khadija; Anisya Dwi Utami Ruppa; Nuraeni Nuraeni; Nurfadillah Nurfadillah (Jurnal Mirai Management, 2023)
UMKM Pia Mirah is a business engaged in the culinary field, which produces various types of Pia cakes. UMKM Pia Mirah still controls raw materials in a simple way so that this makes UMKM Pia Mirah experience difficulties in determining the right inventory. Therefore, UMKM Pia Mirah needs to manage the right raw material inventory with more efficient inventory costs using the EOQ Method. The method used in collecting data is by conducting interviews with the Owner of the Pia Mirah UMKM and documentation which aims to describe and explain using document sources. So it can be concluded that by planning raw materials following the results of the EOQ analysis, UMKM Pia Mirah can make raw material costs more efficient. Key Words: Management, economics, econometrics, EOQ